Nonsurgical Rehabilitation in Dachshunds With T3-L3 Myelopathy: Prognosis and Rates of Recurrence - Sedlacek, Jordan; Rychel, Jessica; Giuffrida, Michelle; Wright, Bonnie (Frontiers in Veterinary Science, 2022)
Dachshunds are at significant risk of experiencing thoracolumbar intervertebral disk herniation during their lifetimes. Standard of care includes advanced imaging, surgical intervention, and postoperative rehabilitation. Conservative management is commonly recommended for cases where standard of care is declined, and little is known on the prognosis of treatment with conservative management and rehabilitation (nonsurgical rehabilitation). This retrospective cohort study assessed 12-week functional outcome and recurrence of clinical signs in 40 dachshunds with T3-L3 myelopathy presumed to be due to Hansen's Type I disc herniation, treated with nonsurgical rehabilitation. Overall prognosis was good with 34 of 40 (85.0%, 95%CI 70.2 – 94.2) dachshunds achieving functional pet status by 12 weeks post-injury. Modified Frankel Score at presentation was significantly (P<0.001) higher in dogs with a positive 12-week outcome compared to dogs that did not recover by 12 weeks. All 27 dogs with motor function at presentation had a positive outcome. Of the 9 dogs exhibiting paraplegia with intact deep nociception at presentation, 7 dogs (77.8%) had achieved a positive outcome by 12 weeks. None of the 4 dogs persistently lacking deep nociception had a positive outcome. Among 27 dogs with a positive outcome for whom follow-up records were available, the 1- and 2-year recurrence rates for T3-L3 myelopathy were 5% and 11%, respectively. Nonsurgical rehabilitation should be considered in dachshunds with mild to moderate T3-L3 myelopathy or in severe cases when advanced imaging and surgical intervention are not possible.